Business accomplishments, gender and entrepreneurial self-image - Ingrid Verheul; Lorraine Uhlaner; A. Roy Thurik (Max Planck Institute for Research into Economic Systems, 2004)
Drawing on Bem's psychological theory of self-perception, this paper presents and tests a model that examines the impact of business accomplishments and gender on entrepreneurial self-image and explores the definition of entrepreneurship according to Vesper's entrepreneu-rial typology. Regression techniques are used to identify those business accomplishments that university alumni associate with self-perceptions of entrepreneurship. Experience as a small business person (founding, running, and/or owning a small business) most clearly predicts en-trepreneurial self-image. Results also support predictions of both direct and indirect effects of gender as well as direct effects of education and business degree. Results of a separate expert panel study are used to rank business accomplishments according to degree of entrepreneur-ship. Results of both studies reveal stark contrasts in the implied definition of entrepreneur-ship between entrepreneurship experts (academic and practitioner alike) and the general busi-ness community (as represented by the alumni). This raises questions about the meaning of the term "entrepreneurship", what the word "entrepreneur", in particular, conveys to the gen-eral public, and the implications for practice and future research.
Keywords: 330; Unternehmer; Selbstständige; Wahrnehmung; Geschlecht; Weibliche Führungskräfte; USA